Parameters of Artificial Intelligence (AI) in Fatwa Issuance: A Jurisprudential and Technological Ethics Analysis - Ahmad Fikri Che Yusoff; Mohd Harifadilah Rosidi (Intelligentia Resources, 2026)
Non-Indexed Publication